KETEPATAN DAN VARIASI PENGGUNAAN PELENGKAP ARAH BAHASA MANDARIN DALAM KARANGAN PEMBELAJAR - Bossy Paskalis; Hana Nurul Hasanah (Center of Language and Cultural Studies, 2018)
This research aims at describing the correct use of directional complements and elaborating the diversity and meanings of compound directional complement (CDC) used in Mandarin learners' interlanguage. This research is a case study on the essay of Universitas Indonesia Chinese Study Program students. Results were obtained through qualitative data analysis method supported by simple calculation. Learners’ accuracy was reflected in identifying the direction of action, ordering the constituents in a sentence with directional complement, and selecting the motion verb. Meanwhile, inaccuracy appeared in four categories: misselection, misordering, overinclusion, and blends. On the other hand, the use of directional complements with literal meaning was very diverse, but not so for the metaphorical ones. Although the frequency of the metaphorical use of CDC was higher than the literal ones, there was a lack of the variation in the type of CDC used by the learners.